2019
DOI: 10.1002/mana.201700429
|View full text |Cite
|
Sign up to set email alerts
|

Amenable Köthe co‐echelon algebras

Abstract: In this note we investigate amenability properties in the class of the so‐called DF‐algebras. We also characterize, in terms of the defining sequence of weights, amenable Köthe co‐echelon algebras.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…We define topologically amenable algebras in terms of topologically flat modules, and we show that topological amenability for complete barrelled DF-algebras is equivalent to amenability in Johnson's sense. We also obtain a topological amenability criterion for Köthe co-echelon algebras, completing thereby recent results of the second author [23,24].…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…We define topologically amenable algebras in terms of topologically flat modules, and we show that topological amenability for complete barrelled DF-algebras is equivalent to amenability in Johnson's sense. We also obtain a topological amenability criterion for Köthe co-echelon algebras, completing thereby recent results of the second author [23,24].…”
Section: Introductionsupporting
confidence: 70%
“…A comprehensive study of Köthe co-echelon spaces may be found in [1]. Köthe co-echelon algebras appear as a main object of investigation in [3] and [23,24].…”
Section: Notation and Preliminariesmentioning
confidence: 99%
“…We define topologically amenable algebras in terms of topologically flat modules, and we show that topological amenability for complete barrelled DF-algebras is equivalent to amenability in Johnson's sense. We also obtain a topological amenability criterion for Köthe co-echelon algebras, complementing thereby recent results of the second author [23,24]. Note that such algebras need not be complete, so that our definition of topological amenability is made in terms of the completion (see Definition 3.21).…”
Section: Introductionmentioning
confidence: 59%
“…(iii) To get the nuclearity of k p (V) we repeat exactly the proof of [23, Theorem 5.1]. We can indeed do so, since π −1 is a topological isomorphism not only in the case of amenability (which was the assumption in [23]) but also under the weaker assumption of topological amenability. ◻ Theorem 4.5 Let 1 ≤ p < ∞ , and let k p (V) be a Köthe co-echelon algebra.…”
Section: Define Now a Linear Mapmentioning
confidence: 81%
See 1 more Smart Citation